2011
DOI: 10.1177/0021998311415444
|View full text |Cite
|
Sign up to set email alerts
|

Determining the through-thickness properties of thick glass fiber reinforced polymers at high strain rates

Abstract: The use of thick fiber reinforced polymer (FRP) laminates in composite armor and naval structures requires thorough characterization of the through-thickness properties of said laminates, both quasi-statically and at high strain rates. Specimens cut from an E-Glass/vinyl ester FRP were tested in compression both quasi-statically and dynamically using a split Hopkinson pressure bar (SHPB). The SHPB tests utilized a conical striker for pulse shaping, to reduce the variation in strain rate during the test. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This amount of scatter is typical of most studies reporting tensile strength measurements using a SHPB at high strain rate such as [4,8,42]. Govender et al [43] used pulse timeshifting to avoid the assumption of quasi-static equilibrium, and produced strength measurements of similar consistency to the current study. However, their approach relied on predicted stresses based on 1-D wave theory and no quasi-static values were provided to quantify the strain rate sensitivity.…”
Section: Strength Identificationmentioning
confidence: 62%
“…This amount of scatter is typical of most studies reporting tensile strength measurements using a SHPB at high strain rate such as [4,8,42]. Govender et al [43] used pulse timeshifting to avoid the assumption of quasi-static equilibrium, and produced strength measurements of similar consistency to the current study. However, their approach relied on predicted stresses based on 1-D wave theory and no quasi-static values were provided to quantify the strain rate sensitivity.…”
Section: Strength Identificationmentioning
confidence: 62%
“…SHPB testing was preferred over quasi-static testing, as the high strain rates applied during the SHPB test are more reflective of those encountered in a comminution or milling context. These tests followed the procedure outlined by Bbosa (2007) and Govender et al (2012). After testing different strikers and conditions, the standard conditions for all impacts included using a conical striker (400 mm long, and a mass of 885 g), strain gauge bridge excitation voltage of 2 V, strain gauge amplifier gain of 1000, and sampling rate of 10 megasamples per second (MSa/s).…”
Section: Methodsmentioning
confidence: 99%
“…In order to study spall failure phenomena, a single Hopkinson pressure bar (HPB) may be used instead of the two bar configuration often used for standard SHPB compression tests. Govender et al (2011) demonstrated the spall damage phenomenon for a long rod specimen directly impacted by a projectile. Specimen failure occurs at a location when the resultant stress between the incident compressive stress wave and the reflected tensile stress wave exceeds the tensile strength of the material.…”
Section: Spall Testing With the Sphbmentioning
confidence: 98%